2009
DOI: 10.1897/ieam_2008-053.1
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term, multitrophic level study to assess pulp and paper mill effluent effects on aquatic communities in four us receiving waters: Background and status

Abstract: An industry-funded, long-term, receiving water study was initiated in 1998/1999 to adress questions about the potential effects of pulp and paper mill effluent discharges on US receiving waters. Although the study continues, the knowledge gained to date provides an opportunity to reflect on the study development process, its progress, and its outcomes. As a backdrop to a series of articles in this special issue describing study results, this article describes the process by which study information objectives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A summary of key watershed features and variables for the 4 streams is provided in Table 4. One of the selection criteria for the 4 study sites was that they provide an opportunity to address questions of effluent effects in the clearest possible manner (Hall et al 2009). Although this eliminated locations with multiple industrial dischargers or major municipal discharges, it did not necessarily address other potentially confounding watershed variables (see Table 4), some of which may create challenges in addressing effluent‐specific questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A summary of key watershed features and variables for the 4 streams is provided in Table 4. One of the selection criteria for the 4 study sites was that they provide an opportunity to address questions of effluent effects in the clearest possible manner (Hall et al 2009). Although this eliminated locations with multiple industrial dischargers or major municipal discharges, it did not necessarily address other potentially confounding watershed variables (see Table 4), some of which may create challenges in addressing effluent‐specific questions.…”
Section: Discussionmentioning
confidence: 99%
“…A study was initiated in 1998/1999 to address questions about the environmental compatibility of pulp and paper mill effluent discharges with diverse and sustainable receiving‐water aquatic communities. Hall et al (2009) provides background on these studies on questions about formulation and specific objectives, and a series of articles follows in this issue on periphyton (Flinders, Minshall, Hall, et al 2009), macroinvertebrate (Flinders, Minshall, Ragsdale, et al 2009), and fish community (Flinders, Ragsdale, and Hall 2009) findings and on fish laboratory life‐cycle tests (Borton et al 2009). This article provides background for the receiving waters studied, including their chemical and physical water quality conditions, the associated pulp and paper mills and their effluent discharges, and the matrix of sample locations and monitoring parameters for each stream.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the first 9 y of the LTRWS are summarized in the 8 papers presented in this special section of Integrated Environmental Assessment and Management. The opening paper by Hall et al (2009a) sets the stage by reviewing the mission of the LTRWS. Information objectives include addressing pulp and paper mill effluent effects at the population/community level within both a temporal (>10 y) and watershed scale.…”
Section: Editor's Notementioning
confidence: 99%
“…As such, there remains a strong need for long-term characterizations of the nature and magnitude of variation in biological and water quality endpoints in surface waters in order to better support water quality management decision-making (Burt et al 2010;Milly et al 2008). Flinders et al (2015) present information on the variability of several biological endpoints found in a long-term study initiated in 1997 in four US streams to evaluate abiotic and biotic changes related to inputs of pulp and paper mill effluent (Hall et al 2009a). This study, referred to as the long-term receiving water study (LTRWS), adopted an integrative approach that examined both environmental characteristics (i.e., water quality measurements and physical habitat assessments) and community-level assessments of fish, benthic macroinvertebrates, and periphyton conducted using spring and fall samples.…”
Section: Introductionmentioning
confidence: 99%